Integrated thermal hydrolysis pretreated anaerobic digestion centrate and municipal wastewater treatment via partial nitritation/anammox process: a promising approach to alleviate inhibitory effects and enhance nitrogen removal - Cao, Shenbin (2022)
Two-stage Partial nitritation/Anammox (PN/A) was firstly performed for recalcitrant organics (RO)-rich thermal hydrolysis pretreated anaerobic digestion (THP-AD) centrate treatment with municipal wastewater (MW) as co-substrate. Results indicated the inhibitory effects of RO was alleviated and high nitrate issue in PN/A effluent was addressed by cotreatment strategy. Stable PN with nitrite accumulation ratio of 95% and N removal efficiency of 97.1% were well maintained at MW of 80%. Nevertheless, nitrate accumulation and anammox activity loss were observed with lowering MW proportion owing to the weakened denitrification activity and aggravated inhibitory effect. Microbial analysis revealed Nitrosomonas was the major ammonium oxidizing bacteria and the ideal PN performance was due to the effective out-selection of nitrite oxidizing bacteria. Candidatus Kuenenia was identified as the primary bacteria for nitrogen removal (82.7%), and the controlled abundance of heterotrophic denitrifiers in anammox system ensured the enhanced nitrogen removal regardless of high COD loading from THP-AD centrate.